Preparation of Osmotically Dehydrated Tender Jackfruit Cube - Chattopadhyay, Priyam; Paul, Praddut Kr.; Mishra, Sukanya; Devi, M. Preema; Ghosh, Swapan (International Journal of Bio-resource and Stress Management, 2018)
A laboratory experiment was conducted during 2014–16, in Department of Pomology and Post Harvest Technology, Uttar Banga Krishi Viswavidyalaya for preparation of osmotically dehydrated tender jackfruit cube. India is the second largest producer of fruits and vegetables after China, but 70% of fruits and vegetables output is wasted, accounting for 40% of the total cost. Jackfruit is one of the leading wasted commodities in India. Due to presence of high moisture content, the fruit is very perishable in nature and being a bulky fruit its transportation is not very easy and is costly as well. Keeping the above points in view, the present investigation was carried out to make this nutritious food available through out the year, to check its rapid wastage and to increase its shelf life. For the preparation of osmotically dehydrated jackfruit cube, independent variables were Salt concentration (1–15%), time (30.00–240.00 min) and Ca(OH)2 concentration (0 and 1%), and the response variable were Water loss (%), mass reduction (%), change in dry matter content (%), water activity and rehydration ratio. For this experiment the highest amount of water loss (90.54%) was observed in run 13, mass reduction was highest (91.61%) in Run 18, highest amount of Change in dry matter (37.26%) was found in run 19 and rehydration ratio (3.77) was in Run 10. The lowest amount of water activity (0.724 aw), was observed in run 15. For the evaluation of storage study of immature jackfruit cube, water activity, rehydration ratio and total plate count were estimated as experimental parameter and was recorded for 6 month at 1 month interval.